Watching More Closely: Shot Scale Affects Film Viewers’ Theory of Mind Tendency But Not Ability - Rooney, Brendan; Bálint, Katalin E. (Frontiers in Psychology, 2018)
Recent research debates the effects of exposure to narrative fiction on recognition of mental states in others and self, referred to as Theory of Mind. The current study explores the mechanisms by which such effects could occur in fictional film. Using manipulated film scenes, we conducted a between subject experiment (N=136) exploring how film shot-scale affects viewers’ Theory of Mind. Specifically, in our methods we distinguish between the trait Theory of Mind abilities (ToM ability), and the state-like tendency to recognise mental states in others and self (ToM tendency). Results showed that close-up shots (compared to long shots) of a character was associated with higher levels of Theory of Mind tendency, when the facial expression was sad but not when it was neutral. And this effect did not transfer to other characters in the film. There was also no observable effect of character depiction on viewers’ general Theory of Mind ability. Together the findings suggest that formal and content features of shot scale can elicit Theory of Mind responses by directing attention towards character mental states rather than improving viewers’ general Theory of Mind ability.